Whole-Genome Sequencing of a Colistin-Resistant Acinetobacter baumannii Strain Isolated at a Tertiary Health Facility in Pretoria, South Africa - Noel-David Nogbou; Mbudzeni Ramashia; Granny Marumo Nkawane; Mushal Allam; Chikwelu Lawrence Obi; Andrew Munyalo Musyoki (MDPI AG, 2022)
Background: Acinetobacter baumannii's (A. baumannii) growing resistance to all available antibiotics is of concern. The study describes a colistin-resistant A. baumannii isolated at a clinical facility from a tracheal aspirate sample. Furthermore, it determines the isolates' niche establishment ability within the tertiary health facility. Methods: An antimicrobial susceptibility test, conventional PCR, quantitative real-time PCR, phenotypic evaluation of the efflux pump, and whole-genome sequencing and analysis were performed on the isolate. Results: The antimicrobial susceptibility pattern revealed a resistance to piperacillin/tazobactam, ceftazidime, cefepime, cefotaxime/ceftriaxone, imipenem, meropenem, gentamycin, ciprofloxacin, trimethoprim/sulfamethoxazole, tigecycline, and colistin. A broth microdilution test confirmed the colistin resistance. Conventional PCR and quantitative real-time PCR investigations revealed the presence of adeB, adeR, and adeS, while mcr-1 was not detected. A MIC of 0.38 µg/mL and 0.25 µg/mL was recorded before and after exposure to an AdeABC efflux pump inhibitor. The whole-genome sequence analysis of antimicrobial resistance-associated genes detected beta-lactam: blaOXA-66; blaOXA-23; blaADC-25; blaADC-73; blaA1; blaA2, and blaMBL; aminoglycoside: aph(6)-Id; aph(3")-Ib; ant(3")-IIa and armA) and a colistin resistance-associated gene lpsB. The whole-genome sequence virulence analysis revealed a biofilm formation system and cell-cell adhesion-associated genes: bap, bfmR, bfmS, csuA, csuA/B, csuB, csuC, csuD, csuE, pgaA, pgaB, pgaC, and pgaD; and quorum sensing-associated genes: abaI and abaR and iron acquisition system associated genes: barA, barB, basA, basB, basC, basD, basF, basG, basH, basI, basJ, bauA, bauB, bauC, bauD, bauE, bauF, and entE. A sequence type classification based on the Pasteur scheme revealed that the isolate belongs to sequence type ST2. Conclusions: The mosaic of the virulence factors coupled with the resistance-associated genes and the phenotypic resistance profile highlights the risk that this strain is at this South African tertiary health facility.